İlişkisel belirsizliğin ilişki istikrarı üzerindeki diyadik etkisinin incelenmesi - Kamalak, Ömer (Hasan Kalyoncu Üniversitesi, 2021)
Bu çalışmanın ilk amacı romantik ilişkisi bulunan bireylerin ilişkisel belirsizlik alanlarının belirlenmesidir. İkinci amacı ise romantik çiftlerde ilişkisel belirsizliğin ilişki istikrarının belirleyicisi olan ilişki doyumu, alternatiflerin kalitesi ve yatırım miktarı değişkenlerini açıklamadaki rolünün Aktör-Partner Karşılıklı Bağımlı Model çerçevesinde incelenmesidir. Araştırmanın amaçlarını gerçekleştirmek için iki farklı araştırma grubu oluşturulmuştur. Birinci amacı gerçekleştirmek için oluşturulan 335 kişilik romantik ilişki içerisinde olan partner grubundan 90 çift (n = 180 birey) ikinci araştırma grubu için seçilmiştir. Araştırmada kullanılan veri toplama araçları Kişisel Bilgi Formu, İlişkisel Belirsizlik Ölçeği ve İlişki İstikrarı Ölçekleridir. Araştırma sonuçlarına göre bireyleri yaşadığı romantik ilişkide en çok belirsizliğe düşüren alanlar; uzak mesafeli ilişki yaşama, iletişim sorunları ve kariyer hedefleri alanlarıdır. Bununla birlikte, romantik ilişkisi olan çiftlerin ilişkisel belirsizliği ile ilişki doyumları, alternatiflerin kalitesi ve yatırım miktarları arasında aktör-partner etkileri bulunmuştur. Elde edilen bulgular ilgili alanyazın ışığında ve Belirsizliği Azaltma Teorisi bağlamında tartışılmış ve gelecekteki çalışmalar ve uygulayıcılara önerilerde bulunulmuştur.

The first aim of this study is to examine the relational uncertainty areas of individuals in romantic relationships. The second aim is to examine the role of perceived relational uncertainty in explaining the determinants of relationship commitment: relationship satisfaction, the quality of alternatives, and the investment size in a dyadic context. For this purpose, the Actor Partner Interdependence Model was conducted to reveal the effects of perceived relational uncertainty on both individuals' relationship commitment variables (actor effect) and their partners' relationship commitment variables (partner effect). Two different research groups were formed to achieve the aims of the study. The first research group consists of 335 individuals who were currently in a romantic relationship. Ninety couples (n = 180 individuals) who participated to the first study group as a couple were picked from the first study group. The data collection tools used in this study were Demographic Information Form, the Relational Uncertainty Scale, and the Relationship Stability Scale. The data were analyzed via SPSS 26.0 and AMOS 26.0. According to the results of the study, having long-distance relationships, communication issues, and career goals were reported as the most common areas of relational uncertainty. Additionally, perceived level of relational uncertainty was found to have a significant and positive influence on relationship satisfaction and investment size both for women and men (actor effect). However, this result was found to be non-signifcant for partner effects. Individuals' perceived level of relational uncertainty, for women and men, was found to have a significant and positive influence on both individuals' (actor effect) and their partners' (partner effect) evaluations for quality of alternatives. The results of the study were discussed in the context of the relevant literature and Relational Uncertainty Theory. Implications for theory, research, and practice and recommendations for future studies were presented.
The examination of the dyadic effect of relational uncertainty on relationship stability
Keywords: Psikoloji; Psychology